Synthesis and physical-chemical properties of 3-(alkylthio)-4-R-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazoles - O. A. Suhak; O. I. Panasenko; Ye. G. Knysh (Zaporozhye State Medical University, 2015)
Aim. Selection, synthesis and biological properties of new compound play major role in creating original medicines. Methods and results. Therefore, to find new bioactive compounds 3-(alkylthio)-4-R-5-(thiophene-2-ylmethyl)-4H-1,2,4-triazoles, where R - methyl, ethyl, phenyl, have been synthesized, by alkylation reaction of 4-R-5-(thiophene-2-ylmethyl)-4H-1,2,4-triazole-3-thiols with 1-bromobutane, or 1-bromopentane, or 1-bromohexane, 1-bromoheptane, 1-bromooctane, 1-bromononane, 1-bromodekane in the n-butanol medium and their physical-chemical properties have been studied using modern physical-chemical methods of analysis, elemental analysis, IR spectroscopy, and their individuality using HPLC-MS. Conclusion. This suggests the possibility of further studying the biological effect of the synthesized compounds.